(untitled) (Asian Journal of Pharmaceutics (AJP), 2021)
Aim: The aim of the study is to synthesize two new hexaureachromium complexes: [Cr(CO(NH2 ) 2 ) 6 ](HCO3 ) 3 (1), [Cr(CO(NH2 ) 2 ) 6 ] 2 (CO3 ) 3 (2) followed by the analysis of binding ability of hexaureachromium(III) cation towards carbonated anions ( 2 HCO and CO 3 3 − − ) and their antimicrobial activities against Escherichia coli, Staphylococcus aureus S. aurses (for anti-bacterial), and Aspergillus niger (for anti-fungal). Materials and Methods: The synthesized compounds 1 and 2 were characterized by spectroscopic studies (fourier-transform infrared and ultraviolet [UV]- visible). The binding properties of [Cr(CO(NH2 ) 2 ) 6 ] 3+ ([HuCr]3+) with carbonated anions ( 2 HCO and CO 3 3 − − ) in aqueous medium have been determined with standard UV–visible spectrophotometerthrough titration method. Further, the stoichiometric ratios for complexes 1 and 2 were found through Job’s plot. All compounds were also tested for antimicrobial activity against selected strains. Results and Discussion: The cation, [HuCr]3+, contains ligand urea bearing H-bond donors which are capable of forming hydrogen bonds. The binding constant values obtained are found to be 10.5334 for and 15.7377 for . Further, the stoichiometric ratios for complexes 1 and 2 have been found to be 1:3 and 2:3, respectively. [HuCr]Cl3 , 1 and 2 show the maximum zone of inhibition at 200 μg/mL but the starting material [HuCr]Cl3 and compound 1 does not show any activity against A. niger at 50 and 100 μg/mL concentration. Conclusion: The ionic reactions between anion receptor [HuCr]3+ and carbonated anions in aqueous solution have been investigated and characterized by spectroscopic (infrared and UV–visible) techniques. The results obtained indicate that the binding ability of the cation [HuCr]3+ towards carbonated anions is in the order 2 CO3 − > HCO3 − . Thus, the selectivity of receptors for particular anion can be chosen. The results predict that the octahedral geometry of [HuCr]3+ is capable enough to target both the carbonated anions. [HuCr]Cl3 and compound 1 do not show any activity against A. niger at 50 and 100 μg/mL concentration while compound 2 is found to be potent against all the tested organisms (E. coli, S. aurses, and A. niger).